Digital Educational Technologies: Market Ends or Means at the Service of Critical Learning? - Gómez Torres, Juan Rafael (Revista Ensayos Pedagógicos, 2022)
This essay intends to show that digital technologies have their own goals since their creation and that some possible consequences of their indiscriminate use in education are misinformation, solipsism, loss of privacy and labor rights, the instrumentalization of reason and life, generating benefits for a few companies and business people that promote them to accumulate riches concentrated in few hands. From this reality, we propose that their use be revised so that their application does not follow parameters issued by big companies, financial entities, or neoliberal governments, that they be used critically, ethically, and politically to benefit those that have fewer opportunities, nature itself, those that are unprivileged, and social justice to reach an ethical, aesthetic, and transformative learning.